Pakistan : Punjab Economic Report, Towards a Medium-Term Development Strategy - World Bank (Washington, DC, 2012)
The report aims analyze the development strategy of the government of Punjab. The report begins by examining the main elements of its economic strategy. This strategy will rest on five pillars: (1) improving governance; (2) reforming the fiscal and financial management system; (3) creating a more supportive environment for private sector-led growth; (4) improving the delivery of public services; and (5) addressing the provincial economy's vulnerability to shocks. Taken together, these elements add up to a strategy that is occupied not only with increasing output, but also emphasizes education, health, improved governance, and protection of the environment. The overriding concern is to provide a better life for the province's citizens. In the short- to medium-term, the provision of a better life to the Punjab's citizens depends essentially on two considerations. First, incomes must be increased; second, the delivery of public services must be improved.